Overview of Covid – 19 Vaccination Coverage in the Working Area of Karawang Health Center Sukabumi Regency Period July Year 2022 - Ofian Ismana; Nurhayati; Linawati Handayani; Davi Sundari (International Journal of Scientific Multidisciplinary Research, 2023)
High and even coverage of Covid-19 vaccination is the key to success. If the vaccination coverage is high and evenly distributed, herd immunity can be formed, and cross-protection can be created. Cross-protection is a condition in which a person still gets the benefits of protection against the risk of contracting a disease even though he is not vaccinated because he is in a community where the majority have already been vaccinated. As a result, it will reduce the virus's spread, break the transmission chain, and ultimately stop this disease